(untitled) (Nepalese Journal of Development and Rural Studies, 2018)
This study explains prospects and constraints of pilgrimage tourism at Santaneshwor Mahadev temple located in Godavari Municipality, Lalitpur. In doing so, quantitative case study methodology is applied. Necessary data are collected from 123 respondents (60 local residents, 60 tourists & 3 hotel owners) selected convenniencely, randomly and purposively. The result indicates that this temple is famous from religious and cosmological view points. And also famous for becoming 360 degree scenic view points having good networking of road accessibility. Tourist arrival in the study area is favorable in all season. However, tourism activities in this area found minimum. Majority of the local people belongs to Brahman caste and engaged in subsistence farming. They have no clear-cut idea for developing and promoting tourism activities. There is lack of basic tourist facilities like; tourist center, modern toilets, clean drinking water, restaurants, accommodation facilities, foreign exchange etc. Hence, awareness programs should be implemented in local communities and different facilities must be offered for promoting religious tourism. And better to prepare master plan by concerned authority to make Santaneshwor Mahadev temple as attractive pilgrimage tourism destination.